Parental Monitoring, Behavioral Problems, and School Achievement of Belgrade Secondary School Students - Nikoleta M. Gutvajn; Marina M. Kovačević Lepojević (University of Belgrade, Teacher Education Faculty, 2020)
Differences in student school achievement are associated with many factors, the most significant ones being: family, school, and personal characteristics of students. Social relations within the family, especially between parents and children, are often associated in the literature with various aspects of school adjustment and the level of student achievement. The aim of this research is to investigate the correlation between school achievement, parental monitoring and externalizing behavioral problems of Belgrade secondary school students. The sample consists of 507 students aged 15 to 18, of both sexes. The data on externalizing problems were collected using ASEBA YSR / 11-18, and on parental monitoring by using the Parental Monitoring Scale. The mid-term scores of the secondary school students were taken as a criterion for school achievement. Hierarchical multivariate regression analysis showed that the examined variables explain 13.9% of the examined variance of school achievement, while the most significant effects were observed regarding age (β = 0.165) and self-disclosure (β = 0.210). The results of the research are indicative of the need for improving the cooperation between the family and the school.